Mengembangkan Literasi Keuangan Masyarakat melalui Webinar ‘Kenali Fintech Lending Legal dan Ilegal’ - Vita, Elisabeth; Dema, Yosef; Birowo, Sigit; Hendratmoko (Jurnal Abdimas: Sosial, Bisnis, dan Lingkungan, 2024)
Celebrating the innovation and creativity in the Fintech space, the webinar, 'Understanding Legal and Illegal Fintech,' is a dynamic exploration led by seasoned industry experts. With a focus on the intricate legal and ethical dimensions of financial technology, participants will gain invaluable insights to navigate this rapidly evolving landscape responsibly. From dissecting legal frameworks to delving into compliance requirements and regulatory nuances, the webinar provides a solid foundation. Furthermore, it offers practical strategies for identifying and mitigating risks associated with illegal practices, while also stressing the importance of consumer empowerment and community support in Fintech lending. Through engaging presentations, real-life case studies, and interactive discussions, attendees will not only grasp the importance of legal compliance and ethical practices but also gain a deeper understanding of consumer protection in the realm of Fintech.